A ludological and narrotological analysis of crime representations in digital games - Nizam, Feridun (IGI Global, 2024)
For a long time, the representation of crime in various media channels has been the subject of many studies. The studies conducted are mainly on news content. However, crime is represented not only in the news but also in many different media and content. One of these channels is digital games. According to the latest data released by Statista, 3.24 billion people are currently playing games worldwide. It is also stated that 48% of computer owners currently use the device to play video games. It is understood that digital games have a very important place in the process-they evolved from analogue games to digital games-and the market share they have and the size of the audience they can reach. Digital games, which have many categories and can reach a large number of people, produce and present representations of crime like other media types. There are not many studies on crime representations in digital games, which is an important branch of new media. This study aims to reveal the ways of production and presentation of crime representations in digital games. © 2024, IGI Global. All rights reserved.